Biophysical Mechanisms of Membrane-Thickness-Dependent MscL Gating: An All-Atom Molecular Dynamics Study - Katsuta, Hiroki; Sawada, Yasuyuki; Sokabe, Masahiro (Langmuir, 2019)
The bacterial mechanosensitive channel, MscL, is activated by membrane tension, acting as a safety valve to prevent cell lysis against hypotonic challenge. It has been established that its activation threshold decreases with membrane thickness, while the underlying mechanism remains to be solved. We performed all-atom molecular dynamics (MD) simulations for the initial opening process of MscL embedded in four different types of lipid bilayers with different thicknesses: 1,2-dilauroyl-sn-glycero-3-phosphocholine (DLPC)), 1,2-dimyristoyl-glycero-3-phosphorylcholine (DMPC), 1,2-dipalmitoyl-sn-glycero-3-phosphocholine (DPPC), and 1,2-distearoyl-sn-glycero-3-phosphocholine (DSPC). In response to membrane stretching, channel opening occurred only in the thinner membranes (DLPC and DMPC) in a thickness-dependent way. We found that the MscL opening was governed by the rate and degree of membrane thinning and that the channel opening was tightly associated with the tilting of transmembrane (TM) helices of MscL toward the membrane plane. Upon membrane stretching, the order parameter of acyl chains of thinner membranes (DLPC and DMPC) became smaller, whereas other thicker membranes (DPPC and DSPC) showed interdigitation with little changes in the order parameter. The decreased order parameter contributed much more to membrane thinning than did interdigitation. We conclude that the membrane-thickness-dependent MscL opening mainly arises from structural changes in MscL to match the altered membrane thickness by stretching.